EKOSISTEM HALAL DAN PEMBERDAYAAN UMKM SYARIAH DI YOGYAKARTA - Dian Milasari (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Interesting dimensions in study economy day this in Indonesia is economy Islam with a basic halal ecosystem , within a number of study This become the direction and topic are very urgent, the dynamics are there for example is happen halal potential in various field , Law Movement Protection consumer on a halal basis already give room the existence of BPJH which exists and is based in the Ministry of Religion, even though discussion related with This There are still very pros and cons , reality his is Once found writer in Confefence of Law at UGM final year then , who found that campuses secular and general still very much “ against ” the study about Halal _ or even halal ecosystem objective For protection consumers , regardless from Therefore , the halal protection movement deserves to be appreciated as an interesting movement is halal labeling of MSMEs due to the victories that have been achieved intensively since 2 years last , and this paper try see matter This in dimensions inner city of Yogyakarta dimensions This There is two question research that is being carried out , first how? halal concept in Indonesia? and second How halal ecosystem , and empowerment of sharia MSMEs in the city of Yogyakarta? with use method content analysis For explain draft Halal ecosystem and field data are described For explain Empowerment of Sharia MSMEs in Yogyakarta, results study This is know draft Halal ecosystem in Indonesia, and empowerment of Sharia MSMEs in DI Yogyakarta